FORENSIC IDENTIFICATION THROUGH TOOTH DISCOLORATION AND ALIGNMENT - Seema, Nighat; Jadoon, Omair; Shireen, Fatima; Ahmad, Iftikhar; Shazia, Salma; Hassan, Raheel; Khan, Akbar (Journal of Ayub Medical College Abbottabad, 2020)
Background: Due to poor oral hygiene and use of tobacco, dental discolorations are present in some people and may indicate presence of toxic substances in food or body, while some have anatomical faulty alignment of teeth. The objective of the study was to know the frequency of these discolorations and faulty dental alignment in the target population so that a forensic tool could be developed. Methods: A cross sectional descriptive study was done in the Dentistry Department of ayub teaching hospital Abbottabad during the month of October 2019, on routine patients visiting the department, using non-probability convenience sampling. A Performa was made to be filled by dentists examining their patients using the standard dentition chart to locate teeth; notation chart was used for recording observations. The preliminaries along with sub-variables were recorded in the Performa for each of 101 patients observed; data were analyzed by SPSS 20 for descriptive statistics. Results: Of 101 subjects examined, 54.5% were males and 45.5% females; the percentage of good, satisfactory, and bad hygiene among patients was 12.9%, 11.9%, and 75.2% respectively, with a significant difference of poor oral hygiene among males (p=0.034). Dental discoloration was present in 87.1% of patients, with a significant male dominated gender difference (p=0.038). Faulty alignment was present in 37.6%, as an independent variable. Conclusion: Dental discolorations and faulty alignment of teeth can be utilized as useful tools in exclusionary method of identification which can be used in living and dead for investigation of identification. It was also observed that there is need to emphasize on community dental hygiene in our hospitals. Keywords: Tooth discoloration; Malocclusion; Tooth crowding; Open bite; Cross bite; Over bite